Determinant Factors of Household Poverty - Khairati, Rusda; Syahni, Rahmat (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Poverty rate in Indonesia still relatively high reaches 10,12 % of Indonesia Population. In West Sumatera as a part of Indonesia, the poverty rate although lower than Indonesia, but it is still relatively high, reaches 6.75%. Several programs have been done to cope with poverty in Indonesia which have been successful to decrease the rate of poverty. However, in West Sumatera, the rate of poverty is stagnant in the last 5 years, even increase in the year 2016. To arrange the programs in FP villages, information about poverty is required. Among the important information needed are the factors that affect poverty in FP villages. A family planning village (FP village) is a village selected using certain criteria to be a development locality to help communities improve their quality of life and welfare through family planning and family development program in Indonesia. The objectives of this research were to describe characteristics of poor and non-poor households and to identify determinant factors of household poverty in FP villages of West Sumatera Province. The research was conducted in 17 FP villages, where 255 sample households were selected using multistage random sampling. Data were collected through interviewing the head of poor and non-poor households from July to September 2018. The dependent variable used in this research was status of household poverty, and independent variables were number of a family member, involvement in family planning program, number of a working family member, number of children under 5 years, age of household head, education of household head, the skill of household head, and working hour of the household head. Data were analyzed using descriptive statistics and logistic regression. The result shows that poor household has more household member, less involved in family planning, fewer household working member, younger household head, a higher number of children under 5 years, lower education, mostly having no technical skill, and higher working hour, while determinant factors of household poverty in FP villages were the number of a family member, involvement in family planning program, age of household head, education of household head, and skill of household head.